Environmental, resident and bystander exposure from spraying applications with unmanned aerial vehicles equipped with flat-fan nozzles or rotary atomizers - Pierre-Henri Dubuis; Céline Villars-Corbex; M. Clare Butler Ellis; H. Christoph Geiser; Jeremy J. Harwood; Marco C. Knobloch; Andrew G. Lane; Aurélie Melgar; Joel D. Stohler; Clive R. Tuck; Helen C. Wheeler; Jürg A. Zarn; et al. (Crop Protection, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Horizon scanning to identify priority research questions for the South African marine shore-based recreational fishery - K Hewett; CS Bova; EC Butler; A-R Childs; MW Farthing; BQ Mann; JB Mann-Lang; AC Winkler; K Hyder; WM Potts (African Journal of Marine Science, 2025)

The behavioural response of an estuarine teleost (Cape stumpnose Rhabdosargus holubi ) to angler bait collection in two adjacent Eastern Cape estuaries, South Africa - EC Butler; B van Heerden; MW Farthing; A-R Childs; WM Potts (African Journal of Marine Science, 2025)

Impact of catch and release on the welfare of bronze seabream Pachymetopon grande in the South African marine shore-based fishery - EC Butler; MW Farthing; CS Bova; A-R Childs; WM Potts (African Journal of Marine Science, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Designing development programmes for climate change and uncertainty in Pacific Melanesia – the role for knowledge brokers - James R. A. Butler; Seona Meharg; Nicky Grigg; Emily J. Barbour; Hannah Barrowman; Danie Nilsson; Samantha Stone-Jovicich (Climate and Development, 2025)

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Contribution of invasive carp (Cyprinus carpio) to fish biomass in rivers of the Murray–Darling Basin, Australia - Hayden T. Schilling; Gavin L. Butler; Katherine J. M. Cheshire; Dean M. Gilligan; Jerom R. Stocks; Jason D. Thiem; David A. Crook (Biological Invasions, 2024)
Following the introduction of the ‘Boolarra’ strain to Australia in the mid 1960’s, Common carp ( Cyprinus carpio ) rapidly spread in waterways across the Murray–Darling Basin (MDB) in southern-eastern Australia. A previous study of the population expansion based upon data up to the early 2000s suggested the carp population may have reached, and was fluctuating around, the ecosystem carrying capacity. It has been widely stated in the scientific literature and media that carp comprise up to 90% of fish biomass in MDB rivers; however, this figure is largely based on sparse data collected in the 1990s and the accuracy of this estimate is uncertain. Here, we analyse three decades (1994–2023) of electrofishing data to estimate the median proportion of total fish biomass contributed by carp across > 1,400 sites in lowland rivers ( 90%) by carp has declined from ≈ 33% of sites in the mid-1990s to ≈ 20% of sites. The proportion of biomass comprised by carp varied depending on the scale of analysis. Across the NSW MDB, carp accounted for a median of 57% (95% CI: 42.5–70.4) of fish biomass at the site level. At the river catchment scale estimates ranged from ≈ 45–66%. In contrast, the median proportion of carp within key rivers ranged from ≈ 46–80%, suggesting that carp can dominate total fish biomass in some rivers for short time-periods. The proportion of biomass contributed by carp at the NSW MDB scale was remarkably stable across decades, suggesting that the carrying capacity of carp may have been reached. Our revised estimates of the contribution of carp to overall fish biomass can facilitate informed debate around the dominance of carp in MDB rivers and provide important information for carp management in the future.

Pleistocene shifts in Great Basin hydroclimate seasonality govern the formation of lithium-rich paleolake deposits - Tripti Bhattacharya; Peter R. Brennan; Daniel E. Ibarra; Catherine A. Gagnon; Kristina L. Butler; Alexa Terrazas; Shaw Miller; Lee Ann Munk; David F. Boutt; Ran Feng; Stephanie N. Bullinger; Lucy Weisbeck (Quaternary Science Reviews, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

The value of adding black carbon to community monitoring of particulate matter - Rebecca A. Sugrue; Chelsea V. Preble; James D.A. Butler; Alaia J. Redon-Gabel; Pietro Marconi; Karan D. Shetty; Lee Ann L. Hill; Audrey M. Amezcua-Smith; Boris R. Lukanov; Thomas W. Kirchstetter (Atmospheric Environment, 2024)

Understanding mechanisms of racial disparities in breast cancer: an assessment of screening and regular care in the Carolina Breast Cancer Study - Matthew R. Dunn; Eman M. Metwally; Sanah Vohra; Terry Hyslop; Louise M. Henderson; Katherine Reeder-Hayes; Caroline A. Thompson; Jennifer Elston Lafata; Melissa A. Troester; Eboneé N. Butler (Cancer Causes & Control, 2024)

Fatty acid production and associated gene pathways are altered by increased salinity and dimethyl sulfoxide treatments during cryopreservation of Symbiodinium pilosum (Symbiodiniaceae) - Joseph K. Kihika; John K. Pearman; Susanna A. Wood; Lesley L. Rhodes; Kirsty F. Smith; Matthew R. Miller; Juliette Butler; Ken G. Ryan (Cryobiology, 2024)

What makes a change agent in environmental conflict transformation? Evidence from rural France - Simon Calla; Lou Lécuyer; James R. A. Butler; Juliette C. Young (Biodiversity and Conservation, 2024)
Transformation of agriculture towards increased sustainability is needed to meet the challenge of declining biodiversity. Nevertheless, stakeholders’ differing perceptions of what sustainability should be, and the multiplicity of possible ways to achieve it can lead to conflictual situations, highlighting the importance of conflict transformation as part of the broader sustainability transformation. If conflict transformation needs to be addressed to prevent the status quo persisting, such processes also reveal the state of social relations and allow us to analyze how collective actions could lead to broader transformations. Using three case studies involving conflicts around pesticide use in the region Bourgogne Franche-Comté (France), we investigate the hypothesis that transformation processes require the engagement of change agents who are motivated and able to overcome barriers to change. Results from 55 in-depth interviews with stakeholders highlight that transformational change depends less on the capacities of a single individual, and more on the mobilization of a plurality of heterogeneous actors (especially farmers, local authorities, and the general public). These actors need to carry out a range of activities that occur with and for others and have an influence on others. According to interviewees, the actors need to engage others, encourage new initiatives, create spaces for knowledge exchanges, and go beyond boundaries. The effectiveness of change agents also depends on the existence of participatory and proactive processes to bring individuals together to create or capitalize on windows of opportunity.

Differences in Intentional Weight Loss Strategies According to Race/ethnicity Among US Women, NHANES 2007 – 2018 - A. Gutierrez; R. Goode; M. Slining; L. Butler (Journal of the Academy of Nutrition and Dietetics, 2023)

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

Forester and Logger Response to Emerald Ash Borer in Massachusetts and Vermont: A Secondary Disturbance - Marla Markowski-Lindsay; Paul Catanzaro; Amanda Robillard; Brett J Butler; David A Orwig; Anthony W D’Amato; Jonathan R Thompson; Danelle M Laflower; Meghan Graham MacLean; Malcolm Itter (Journal of Forestry, 2023)
Forester and logger responses to the invasive emerald ash borer (EAB) could substantially affect regions across the United States. We analyzed forester and logger responses to EAB in Massachusetts and Vermont, exploring characteristics associated with purposeful targeting of substantial ash properties; managing forests differently because of EAB; and regeneration goals. One-third of respondents increased timber sales on ash properties, motivated by ecological, not economic, impacts of EAB. Nearly 60% said EAB changed their management activity in stands with ash; changes influenced by the ecological impact of EAB and not economic factors. Those influenced by EAB’s ecological impact to choose properties with substantial ash were more likely to have increased harvest area size, sawtimber removal, and harvest intensity. Loggers were more likely than foresters to remove small-diameter ash and low-grade trees. Both rated regenerating economically valuable species well adapted to the site as their highest essential priority.

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Effects of a fishery closure and prey abundance on seabird diet and breeding success: Implications for strategic fisheries management and seabird conservation - Kate R. Searle; Charlotte E. Regan; Martin R. Perrow; Adam Butler; Anna Rindorf; Michael P. Harris; Mark A. Newell; Sarah Wanless; Francis Daunt (Biological Conservation, 2023)

Urinary concentrations of metals before and after volcanic eruption: a natural experiment surrounding the eruption of Volcán de Fuego, 2018 - Natalie R. Neumann; Jaime Butler-Dawson; Lyndsay Krisher; Diana Jaramillo; Daniel Pilloni; Greg Waite; Yaqiang Li; Stephen B. Wittels; Kathrin Schilling; Lee S. Newman; Katherine A. James (Environmental Geochemistry and Health, 2023)

Growth portfolios buffer climate‐linked environmental change in marine systems - Steven E. Campana; Szymon Smoliński; Bryan A. Black; John R. Morrongiello; Stella J. Alexandroff; Carin Andersson; Bjarte Bogstad; Paul G. Butler; Côme Denechaud; David C. Frank; Audrey J. Geffen; Jane Aanestad Godiksen; et al. (Ecology, 2023)
Large‐scale, climate‐induced synchrony in the productivity of fish populations is becoming more pronounced in the world's oceans. As synchrony increases, a population's “portfolio” of responses can be diminished, in turn reducing its resilience to strong perturbation. Here we argue that the costs and benefits of trait synchronization, such as the expression of growth rate, are context dependent. Contrary to prevailing views, synchrony among individuals could actually be beneficial for populations if growth synchrony increases during favorable conditions, and then declines under poor conditions when a broader portfolio of responses could be useful. Importantly, growth synchrony among individuals within populations has seldom been measured, despite well‐documented evidence of synchrony across populations. Here, we used century‐scale time series of annual otolith growth to test for changes in growth synchronization among individuals within multiple populations of a marine keystone species (Atlantic cod, Gadus morhua ). On the basis of 74,662 annual growth increments recorded in 13,749 otoliths, we detected a rising conformity in long‐term growth rates within five northeast Atlantic cod populations in response to both favorable growth conditions and a large‐scale, multidecadal mode of climate variability similar to the East Atlantic Pattern. The within‐population synchrony was distinct from the across‐population synchrony commonly reported for large‐scale environmental drivers. Climate‐linked, among‐individual growth synchrony was also identified in other Northeast Atlantic pelagic, deep‐sea and bivalve species. We hypothesize that growth synchrony in good years and growth asynchrony in poorer years reflects adaptive trait optimization and bet hedging, respectively, that could confer an unexpected, but pervasive and stabilizing, impact on marine population productivity in response to large‐scale environmental change.

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Spawning observations of Pomadasys commersonnii in the marine section of the Knysna estuarine bay, Western Cape, South Africa - EC Butler; A-R Childs; MKS Smith; RM Foster; WM Potts (African Journal of Marine Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Quantifying the impacts of abrasion and bacterial transfer when fish are exposed to sand during a catch-and-release event - RM Foster; A-R Childs; M Brooks; MW Farthing; EC Butler; WM Potts (African Journal of Marine Science, 2020)

Time-course of the physiological-stress response in bronze bream Pachymetopon grande following a simulated catch-and-release angling event - BA Pringle; A-R Childs; EC Butler; AC Winkler; MI Duncan; C Teta; WM Potts (African Journal of Marine Science, 2020)

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Evaluating the effects of catch-and-release angling on Cape stumpnose Rhabdosargus holubi in a South African estuary - NK Arkert; A-R Childs; MC Parkinson; AC Winkler; E Butler; S Mannheim; WM Potts (African Journal of Marine Science, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Vulnerability of forests of the Midwest and Northeast United States to climate change - Chris Swanston; Leslie A. Brandt; Maria K. Janowiak; Stephen D. Handler; Patricia Butler-Leopold; Louis Iverson; Frank R. Thompson III; Todd A. Ontl; P. Danielle Shannon (Climatic Change, 2018)

Adaptation pathways: ecoregion and land ownership influences on climate adaptation decision-making in forest management - Todd A. Ontl; Chris Swanston; Leslie A. Brandt; Patricia R. Butler; Anthony W. D’Amato; Stephen D. Handler; Maria K. Janowiak; P. Danielle Shannon (Climatic Change, 2018)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Wheat cultivar susceptibility to Gaeumannomyces graminis var. tritici and influence on Pseudomonas fluorescence numbers in the rhizosphere - R. F. van Toor; S. Chng; R. M. Warren; R. C. Butler; M. G. Cromey; R. A. Craigie; B. L. McCloy (Australasian Plant Pathology, 2016)

Development and testing of a micro wind tunnel for on-site wind erosion simulations - Craig L. Strong; John F. Leys; Mike R. Raupach; Joanna E. Bullard; Hélène A. Aubault; Harry J. Butler; Grant H. McTainsh (Environmental Fluid Mechanics, 2016)

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation - James R. Butler; Gregory R. Martens; Jose L. Estrada; Luz M. Reyes; Joseph M. Ladowski; Cesare Galli; Andrea Perota; Conor M. Cunningham; Matthew Tector; A. Joseph Tector (Transgenic Research, 2016)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

Bench-Scale and Pilot-Scale Treatment Technologies for the Removal of Total Dissolved Solids from Coal Mine Water: A Review - Patricio X. Pinto; Souhail R. Al-Abed; David A. Balz; Barbara A. Butler; Ronald B. Landy; Samantha J. Smith (Mine Water and the Environment, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Quantitative PCR to detect Gaeumannomyces graminis var. tritici in symptomatic and non-symptomatic wheat roots - S. Keenan; M. G. Cromey; S. A. Harrow; S. L. Bithell; R. C. Butler; S. S. Beard; A. R. Pitman (Australasian Plant Pathology, 2015)

Life cycle assessment of adsorbents for fluoride removal from drinking water in East Africa - Teshome L. Yami; Junyi Du; Laura R. Brunson; Jim F. Chamberlain; David A. Sabatini; Elizabeth C. Butler (The International Journal of Life Cycle Assessment, 2015)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Quantifying Florida Bay Habitat Suitability for Fishes and Invertebrates Under Climate Change Scenarios - Kelly A. Kearney; Mark Butler; Robert Glazer; Christopher R. Kelble; Joseph E. Serafy; Erik Stabenau (Environmental Management, 2015)

Atlantic bluefin tuna Thunnus thynnus feeding ecology in the northern Gulf of Mexico: a preliminary description of diet from the western Atlantic spawning grounds - C. M. Butler; J. M. Logan; J. M. Provaznik; E. R. Hoffmayer; M. D. Staudinger; J. M. Quattro; M. A. Roberts; G. W. Ingram; A. G. Pollack; M. E. Lutcavage (Journal of Fish Biology, 2015)
A combination of stomach contents, nitrogen stable‐isotope and tissue C:N values are presented to demonstrate feeding activity of Atlantic bluefin tuna Thunnus thynnus on the Gulf of Mexico (GOMEX) spawning grounds. Diets include teleosts, cephalopods, crustaceans and a pelagic tunicate ( Pyrosoma atlanticum ). Results reveal the need to classify the GOMEX as a T. thynnus feeding ground.

Compounds alone and in combination with yeasts to control Colletotrichum acutatum in apples - Kirsty S. H. Boyd-Wilson; Ruth C. Butler; Peter A. Alspach; Kerry R. Everett; I. P. Shamini Pushparajah; Monika Walter (Australasian Plant Pathology, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Effect of β3 adrenoceptor activation in the basolateral amygdala on ethanol seeking behaviors - T. R. Butler; A. M. Chappell; J. L. Weiner (Psychopharmacology, 2014)

Physiological and functional evaluation of healthy young and older men and women: design of the European MyoAge study - Jamie S. McPhee; Jean-Yves Hogrel; Andrea B. Maier; Enn Seppet; Olivier R. Seynnes; Sarianna Sipilä; Roberto Bottinelli; Yoann Barnouin; Astrid Y. Bijlsma; Helena Gapeyeva; Thomas M. Maden-Wilkinson; Carel G. Meskers; et al. (Biogerontology, 2013)

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Sex differences in neuroadaptation to alcohol and withdrawal neurotoxicity - Lynda Sharrett-Field; Tracy R. Butler; Anna R. Reynolds; Jennifer N. Berry; Mark A. Prendergast (Pflügers Archiv - European Journal of Physiology, 2013)

Invertebrate Community Patterns in Seasonal Ponds in Minnesota, USA: Response to Hydrologic and Environmental Variability - Matthew M. Bischof; Mark A. Hanson; Mark R. Fulton; Randy K. Kolka; Stephen D. Sebestyen; Malcolm G. Butler (Wetlands, 2013)

Effects of different rates of Gaeumannomyces graminis var. tritici inoculum for detecting take-all suppression in soils - S. F. Chng; A. Stewart; M. G. Cromey; S. L. Dodd; R. C. Butler; M. V. Jaspers (Australasian Plant Pathology, 2013)

Less government intervention in biodiversity management: risks and opportunities - Juliette C. Young; James R. A. Butler; Andrew Jordan; Allan D. Watt (Biodiversity and Conservation, 2012)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

The efficacy of detecting variants with small effects on the Affymetrix 6.0 platform using pooled DNA - Charleston W. K. Chiang; Zofia K. Z. Gajdos; Joshua M. Korn; Johannah L. Butler; Rachel Hackett; Candace Guiducci; Thutrang T. Nguyen; Rainford Wilks; Terrence Forrester; Katherine D. Henderson; Loic Le Marchand; Brian E. Henderson; et al. (Human Genetics, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Recommendation of short tandem repeat profiling for authenticating human cell lines, stem cells, and tissues - Rita Barallon; Steven R. Bauer; John Butler; Amanda Capes-Davis; Wilhelm G. Dirks; Eugene Elmore; Manohar Furtado; Margaret C. Kline; Arihiro Kohara; Georgyi V. Los; Roderick A. F. MacLeod; John R. W. Masters; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

How the Conflict between American Psychiatry and Neurology Delayed the Appreciation of Cognitive Dysfunction in Multiple Sclerosis - Michelle A. Butler; John R. Corboy; Christopher M. Filley (Neuropsychology Review, 2009)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Metallothionein Treatment Attenuates Microglial Activation and Expression of Neurotoxic Quinolinic Acid Following Traumatic Brain Injury - R. S. Chung; Y. K. Leung; C. W. Butler; Y. Chen; E. D. Eaton; M. W. Pankhurst; A. K. West; G. J. Guillemin (Neurotoxicity Research, 2009)

Use of weighted reference panels based on empirical estimates of ancestry for capturing untyped variation - Matthew R. L. Egyud; Zofia K. Z. Gajdos; Johannah L. Butler; Sam Tischfield; Loic Le Marchand; Laurence N. Kolonel; Christopher A. Haiman; Brian E. Henderson; Joel N. Hirschhorn (Human Genetics, 2009)

Ancient DNA reveals genotypic relationships among Oregon populations of the sea otter (Enhydra lutris) - Kim Valentine; Deborah A. Duffield; Lorelei E. Patrick; David R. Hatch; Virginia L. Butler; Roberta L. Hall; Niles Lehman (Conservation Genetics, 2008)

Mining and environmental change in Sierra Leone, West Africa: a remote sensing and hydrogeomorphological study - Fenda A. Akiwumi; David R. Butler (Environmental Monitoring and Assessment, 2008)

A Greenhouse Assay for Powdery Scab (Spongospora subterranea f. sp. subterranea) Resistance in Potato - S. J. Baldwin; R. A. Genet; R. C. Butler; J. M. E. Jacobs (Potato Research, 2008)

Visual cortex activation in kinesthetic guidance of reaching - W. G. Darling; R. J. Seitz; S. Peltier; L. Tellmann; A. J. Butler (Experimental Brain Research, 2007)

Transgenic Potato Lines Expressing cry1Ba1 or cry1Ca5 Genes are Resistant to Potato Tuber Moth - S. Meiyalaghan; J. M. E. Jacobs; R. C. Butler; S. D. Wratten; A. J. Conner (Potato Research, 2007)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Sources of Resistance to Phytophthora Pod Rot at the International CocoaGenebank, Trinidad - A. D. Iwaro; D. R. Butler; A. B. Eskes (Genetic Resources and Crop Evolution, 2006)

Biotic interactions as determinants of ecosystem structure in prairie wetlands: An example using fish - Mark A. Hanson; Kyle D. Zimmer; Malcolm G. Butler; Brian A. Tangen; Brian R. Herwig; Ned H. Euliss (Wetlands, 2005)

Changes in the innate immune response of Atlantic salmon, Salmo salar L., exposed to experimental infection with Neoparamoeba sp. - K A Gross; M D Powell; R Butler; R N Morrison; B F Nowak (Journal of Fish Diseases, 2005)
An experiment was conducted to determine the effect of Neoparamoeba sp. infection on the innate immune responses of Atlantic salmon. Atlantic salmon were experimentally infected with Neoparamoeba sp. and serially sampled 0, 1, 4, 6, 8 and 11 days post‐exposure (dpe). Histological analysis of infected fish gill arches identified the presence of characteristic amoebic gill disease lesions as early as 1 dpe with a steady increase in the number of affected gill filaments over time. Immune parameters investigated were anterior kidney phagocyte function (respiratory burst, chemotaxis and phagocytosis) and total plasma protein and lysozyme. In comparison with non‐exposed control fish basal respiratory burst responses were suppressed at 8 and 11 dpe, while phorbol myristate acetate‐stimulated activity was significantly suppressed at 11 dpe. Variable differences in phagocytic activity and phagocytic rate following infection were identified. There was an increase in the chemotactic response of anterior kidney macrophages isolated from exposed fish relative to control fish at 8 dpe. Total protein and lysozyme levels were not affected by Neoparamoeba sp. exposure.

The prevalence of escaped farmed salmon, Salmo salar L., in the River Ewe, western Scotland, with notes on their ages, weights and spawning distribution - J. R. A. BUTLER; P. D. CUNNINGHAM; K. STARR (Fisheries Management and Ecology, 2005)
The prevalence of escaped farmed Atlantic salmon, Salmo salar L., in the River Ewe, western Scotland, was assessed. After the establishment of smolt cages in the catchment and marine cages near the river mouth during 1986–1987, approximately 425 000 parr and smolts, and 122 000 growers have escaped. Between 1987 and 2001, farmed salmon occurred in the rod fishery in 13 of the 15 years, contributing at least 5.8% of the total catch, with a maximum annual frequency of 27.1%. It was estimated that P

Investigating the Relationship Between Site-specific Yield and Protein of Cereal Crops - S. Norng; A. N. Pettitt; R. M. Kelly; D. G. Butler; W. M. Strong (Precision Agriculture, 2005)

Assessment of genetic diversity in isolates of Ciborinia camelliae Kohn from New Zealand and the United States of America - R. F. van Toor; H. J. Ridgway; R. C. Butler; M. V. Jaspers; A. Stewart (Australasian Plant Pathology, 2005)

Effects of dietary supplementation with vitamins C and E on muscle function during and after eccentric contractions in humans - A. Shafat; P. Butler; R. L. Jensen; A. E. Donnelly (European Journal of Applied Physiology, 2004)

Reduced metaphase I associations between the short arms of homoeologous chromosomes in a Hordeum vulgare L. H. bulbosum L. diploid hybrid influences the frequency of recombinant progeny - R. A. Pickering; S. Hudakova; A. Houben; P. A. Johnston; R. C. Butler (Theoretical and Applied Genetics, 2004)

Application of Probability Analysis to Assess Nitrogen Supply to Grain Crops in Northern Australia - R. M. Kelly; W. M. Strong; T. A. Jensen; D. Butler (Precision Agriculture, 2004)

Atlantic salmon, Salmo salar L., previously infected with Neoparamoeba sp. are not resistant to re‐infection and have suppressed phagocyte function - K A Gross; R N Morrison; R Butler; B F Nowak (Journal of Fish Diseases, 2004)
Previous studies have indicated that Atlantic salmon, Salmo salar L., affected by amoebic gill disease (AGD) are resistant to re‐infection. These observations were based upon a comparison of gross gill lesion abundance between previously infected and naïve control fish. Anecdotal evidence from Atlantic salmon farms in southern Tasmania suggests that previous infection does not protect against AGD as indicated by a lack of temporal change in freshwater bathing intervals. Experiments were conducted to determine if previous infection of Atlantic salmon with Neoparamoeba sp. would provide protection against challenge and elucidate the immunological basis of any protection. Atlantic salmon were infected with Neoparamoeba sp. for 12 days then treated with a 4‐h freshwater bath. Fish were separated into two groups and maintained in either sea water or fresh water for 6 weeks. Fish were then transferred to one tank with a naïve control group and challenged with Neoparamoeba sp. Fish kept in sea water had lower mortality rates compared with first time exposed and freshwater maintained fish, however, these data are believed to be biased by ongoing mortalities during the seawater maintenance phase. Phagocyte function decreased over exposure time and freshwater maintained fish demonstrated an increased ability to mount a specific immune response. These results suggest that under the challenge conditions herein described, antigen exposure via infection does not induce protection to subsequent AGD.

Column Studies on Nitrate Removal from Potable Water - A. Darbi; T. Viraraghavan; R. Butler; D. Corkal (Water, Air, & Soil Pollution, 2003)

Abundance of Sorghum Panicle-Feeding Bugs (Hemiptera: Miridae) in Mali and Empirical Relationships with Weather - A. Ratnadass; D. R. Butler (International Journal of Tropical Insect Science, 2003)

Immunostimulatory CpG oligodeoxynucleotides increase resistance against amoebic gill disease in Atlantic salmon, Salmo salar L. - A R Bridle; R Butler; B F Nowak (Journal of Fish Diseases, 2003)

Buccal cells as a source of DNA for comparative animal genomic analysis - R. Brooks; J. Williamson; A. Hensley; E. Butler; G. Touchton; E. Smith (Biotechnology Letters, 2003)

Susceptibility of potato (Solanum tuberosum) cultivars to powdery scab (caused by Spongospora subterranea f. sp. subterranea), and relationships between tuber and root infection - Richard E. Falloon; Russell A. Genet; Andrew R. Wallace; Ruth C. Butler (Australasian Plant Pathology, 2003)

The Use of Inverse Phase Gas Chromatography to Measure the Surface Energy of Crystalline, Amorphous, and Recently Milled Lactose - Helen E. Newell; Graham Buckton; David A. Butler; Frank Thielmann; Daryl R. Williams (Pharmaceutical Research, 2001)

Caffeic Acid-Induced Changes in Plant–Water Relationships and Photosynthesis in Leafy Spurge Euphorbia esula - Richard R. Barkosky; Frank A. Einhellig; Jack L. Butler (Journal of Chemical Ecology, 2000)

Identification of genomic regions associated with stay green in sorghum by testing RILs in multiple environments - Y. Z. Tao; R. G. Henzell; D. R. Jordan; D. G. Butler; A. M. Kelly; C. L. McIntyre (Theoretical and Applied Genetics, 2000)

A surface-associated activity trap for capturing water-surface and aquatic invertebrates in wetlands - Mark A. Hanson; Christiane C. Roy; Ned H. Euliss; Kyle D. Zimmer; Michael R. Riggs; Malcolm G. Butler (Wetlands, 2000)

Mechanisms of Hydroquinone-Induced Growth Reduction in Leafy Spurge - Richard R. Barkosky; Jack L. Butler; Frank A. Einhellig (Journal of Chemical Ecology, 1999)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Epidemiology of communicable disease in small populations - Christopher J. Rhodes; A. R. Butler; Roy M. Anderson (Journal of Molecular Medicine, 1998)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

Temporal patterns and transport processes in recruitment of spiny lobster ( Panulirus argus ) postlarvae to south Florida - C. A. Acosta; T. R. Matthews; M. J. Butler IV. (Marine Biology, 1997)

Condensed tannins in Leucaena and their relation to psyllid resistance - R. A. Wheeler; W. R. Chaney; L. G. Butler; J. L. Brewbaker (Agroforestry Systems, 1994)

Some properties of adenylate kinase from chemolithotrophically grown Thiobacillus novellus - I. R. C. McKellar; A. M. Charles; B. J. Butler (Archives of Microbiology, 1980)

Ultrastructural investigations in the stigonemataceae (cyanophyta) - R. D. Butler; A. Allsopp (Archives of Microbiology, 1972)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)

Sectional notes - H. W. Poulsen; H. G. Zuckerman; C. H. Metzger; W. B. Ward; W. C. Edmundson; E. R. Bennet; R. A. Jehle; A. B. Beaumont; John S. Gardner; E. L. Newdick; Frank W. Hussey; E. J. Wheeler; et al. (American Journal of Potato Research, 1934)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)